2012
DOI: 10.1105/tpc.112.097998
|View full text |Cite
|
Sign up to set email alerts
|

Screening a cDNA Library for Protein–Protein Interactions Directly in Planta

Abstract: Screening cDNA libraries for genes encoding proteins that interact with a bait protein is usually performed in yeast. However, subcellular compartmentation and protein modification may differ in yeast and plant cells, resulting in misidentification of protein partners. We used bimolecular fluorescence complementation technology to screen a plant cDNA library against a bait protein directly in plants. As proof of concept, we used the N-terminal fragment of yellow fluorescent protein-or nVenus-tagged Agrobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 46 publications
(71 reference statements)
0
59
0
1
Order By: Relevance
“…Moreover, the association of VirE2 with ER also suggests that VirE2 may interact with other factors during the trafficking processes. Indeed, a SNARElike protein was found to have a strong interaction with VirE2 (46). It has also been reported that reticulon-domain proteins and a Rab GTPase, both involved in trafficking of proteins through endomembranes, are important for transformation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the association of VirE2 with ER also suggests that VirE2 may interact with other factors during the trafficking processes. Indeed, a SNARElike protein was found to have a strong interaction with VirE2 (46). It has also been reported that reticulon-domain proteins and a Rab GTPase, both involved in trafficking of proteins through endomembranes, are important for transformation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast DNA reporter assay and YTH screens were performed as outlined previously (27). DivIVa and BiFC interaction tests were used to verify each interaction found in the YTH as per previous reports (28,36). An in vitro assay was used to determine the effects of different chemicals on the ability of L. bicolor S238N to colonize poplar roots after 2 wk of contact between the two organisms as per Felten et al (33).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a dilution series of the prey cDNA with a noninteracting cDNA as well as observation of the fluorescence in a time dependent manner after transformation can help to validate the results. To ensure discrimination of true fluorescent signals and artifacts the BiFC signals should be quantified and set into relation to another expressed fluorescent protein, for example a marker protein 7,8 . Another drawback of the BiFC method is, that interactions of the proteins may also be hindered sterically by the relatively large fluorescent tags.…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacteria use a so-called Ti plasmid (tumor inducing) coding for enzymes that mediate the transduction of the gene of interest into plant cells. BiFC is well applicable for soluble as well as for membrane proteins within all cellular compartments and has been successfully used over the past years to identify interacting proteins in vivo as well as to analyze interaction sites within the proteins [7][8][9] . Upon expression of the introduced genes, the interaction of the fluorescent proteins can be visualized directly in leaves, which is suitable for larger cellular structures, such as the endoplasmic reticulum (ER), the plasma membrane or chloroplasts.…”
Section: Introductionmentioning
confidence: 99%